The Role of Family-Centered Care in Pediatric Nursing: Challenges and Best Practices - Mona Ali Alghamdi,; Shwroq Hamad Saad Tabah,; Seham ibrahem Ali,; Dalal Abdullah Al-Anzi,; Ahlam Fawaz Alanezi,; Abdulaziz A.Alrouji,; Sahar ahmad aydhe,; Norah Saeed Awad Alsubaie,; Khulud Mushahhin Ali Almutairi,; Bassam Mejeb AlMutari,; Abdulkarim zarea alanazi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Family-centered care (FCC) is a foundational approach in pediatric nursing that emphasizes collaboration, respect, and partnership between healthcare providers, patients, and their families. It recognizes the unique role families play in a child's care and aims to actively involve them in decision-making and caregiving processes. FCC has been shown to improve patient outcomes, enhance family satisfaction, and foster a supportive environment for pediatric patients. This paper explores the principles of FCC, including respect for family roles and values, partnership and collaboration, effective communication, and family empowerment. It also examines the challenges of implementing FCC, such as institutional barriers, provider misconceptions, emotional demands, and cultural or linguistic differences. Finally, the paper highlights best practices for enhancing FCC, including staff training, policy reforms, interdisciplinary collaboration, emotional support for nurses and families, and the use of technology. By addressing these challenges and adhering to evidence-based strategies, healthcare organizations can successfully integrate FCC into pediatric nursing, creating a more inclusive and compassionate care environment that prioritizes the voices and needs of families.